THE IMPLEMENTATION OF PUBLIC SERVICE MANAGEMENT BY THE CIVIL APPARATUS IN FORT ROTTERDAM - Muhammad Adnan; M. Tahir; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
The aim of this investigation was to determine how civil servants implement public service management at the Cultural Heritage Preservation Center of SouthSulawesi Province.This study employs a qualitative research design with a descriptive approach to depict the research subject without any researcher intervention. Datacollection techniques use observation and interviews. The results of this study show that there isstill a lack of human resources, especially those who deal directly with tourists in implementing public services and the problem of facilities that are also lacking for tourists such as buildings that are rarely open to tourists and also tour guides who are still dominant in serving foreign tourists as well as equipment such asprayer equipment, toilets and seats. However, employees still provide the best service by using SOPs as a basis for service and also a unique approach to tourists by providing online services using the preservation hall website and also tourists get aservice called virtual reality that makes tourists get information before they come to visit cultural heritage sites. In addition, employees are very open, especially to students / students / users who want to do activities in the reserve site area. Therefore, it is recommended to the Cultural Heritage Preservation Center of South SulawesiProvince, in particular, the Public Service and Publication Working Group will organize training sessions on service management for employees, especially those who directly deal with tourists /users.